Cutting-edge multi-level analytical and structural characterization of antibody-drug conjugates: present and future. (3rd April 2019) - Beck, Alain; D'Atri, Valentina; Ehkirch, Anthony; Fekete, Szabolcs; Hernandez-Alba, Oscar; Gahoual, Rabah; Leize-Wagner, Emmanuel; François, Yannis; Guillarme, Davy; Cianférani, Sarah
ABSTRACT: Introduction : The development and optimization of antibody drug conjugates (ADCs) rely on improving their analytical and bioanalytical characterization, by assessing critical quality attributes (CQAs). Among the CQAs, the glycoprofile, drug load distribution (DLD), the amount of unconjugated antibody (D0), the average drug-to-antibody ratio (DAR), the drug conjugation sites and the residual drug-linker and related product proportions (SMDs) in addition to high and low molecular weight species (H/LMWS), and charge variants are the most important ones. Areas covered : The analytical and structural toolbox for the characterization of 1 st, 2 d and 3 d generation ADCs was significantly extended in the last 3 years. Here, we reviewed state-of-the-art techniques, such as liquid chromatography, high resolution native and ion mobility mass spectrometry, multidimensional liquid chromatography and capillary electrophoresis hyphenated to mass spectrometry, reported mainly since 2016. Expert commentary : These emerging techniques allow a deep insight into important CQAs that are related to ADC Chemistry Manufacturing and Control (CMC) as well as an improved understanding of in vitro and in vivo ADC biotransformations. This knowledge and the development of quantitative bioanalytical assays will continue to contribute to early-developability assessment for the optimization of all the ADC components (i.e. antibody, drug, and linker) and help to bring next-generation ADCs into late clinical development and to the market.